Molecular characterisation and additional morphological descriptions of Eimeria spp. (Apicomplexa: Eimeriidae) from brown kiwi (Apteryx mantelli Bartlett). - Coker SM; McInnes K; Vallee E; Biggs P; Pomroy WE; Howe L; Morgan KJ (Springer Nature, 2023)
Brown kiwi (Apteryx mantelli Bartlett), a ratite endemic to New Zealand, is currently listed as "Vulnerable" under the IUCN classification system due to predation by introduced mammals. Operation Nest Egg (ONE) raises chicks and juveniles in predator-proof enclosures until they are large enough to defend themselves. These facilities experience an environmental accumulation of coccidial oocysts, which leads to severe morbidity and mortality of these kiwi. Four species of coccidia have been morphologically described from sporulated oocysts with additional opportunistic descriptions of endogenous stages. This research continues the morphological descriptions of these species of Eimeria with an additional novel morphotype also morphologically described. It also provides the first genetic characterisation targeting the mitochondrial cytochrome c oxidase I (COI) gene. Based on these findings, it was determined there are at least five morphotypes of Eimeria that infect brown kiwi and co-infections are common at the ONE facilities surveyed. The COI amplicon targeted for this study was sufficient to provide differentiation from other members of this genus. Sanger sequencing yielded ambiguous bases, indicating the need for more in-depth sequencing.
Keywords: Animals; Eimeria; Species Specificity; Palaeognathae; New Zealand; Coccidiosis; Mammals